BOYCOTTING ISRAELI-AFFILIATED PRODUCTS: A SADDU DZARI’AH REVIEW - Pramesti, Aulya Dwi; Arif , Achmad; Awalia, Fadhila Tianti Mudi; Kanggas, Fazari Zul Hasmi; Gumilang, Binangkit (Journal of Indonesian Comparative of SyariÆah Law, 2025)
The purpose of this research is to explain the practice of boycotting products affiliated with Israel and to explain the legality of the boycott movement from the perspective of the Saddu Dzari’ah. This research is a qualitative study with a juridical-normative typology. The data collection method in this research is documentary study. Primary data were obtained from the documentation of several news portals discussing the boycott movement of products affiliated with Israel, as well as Turath books discussing the principle of Saddu Dzari'ah. As for the secondary data, it was obtained from journals and previous research that discuss the principle of Saddu Dzari’ah.